Cure Kinetics of a Carbon Fiber/Epoxy Prepreg by Dynamic Differential Scanning Calorimetry - Kaihua Chen; Xiaobao Zhu; Guozhen Zhao; Jing Chen; Shenghui Guo (International Journal of Polymer Science)
Investigating the curing kinetics of a fiber prepreg system is beneficial to the controlling of prepreg laminate curing process. In the present work, a dicyandiamide (DICY)-cured carbon fiber/epoxy prepreg system was investigated by non-isothermal differential scanning calorimetry (DSC) at 2, 5, 10, and 20°C/min to attain the glass transition temperature for uncured prepreg and fully cured sample, which were estimated to be 7.6°C and 106.2°C, respectively. The activation energy (Ea) of the prepreg system was evaluated by Kissinger and Ozawa methods, and Friedman method was also employed to reveal the evolution of Ea as a function of curing degree. The kinetic parameters were determined by fitting the average Ea value obtained by Friedman method into Málek methodology, and the two parameters Šesták–Berggren model was found to best describe the curing kinetic of the prepreg system. The preexponential factor was calculated to be 6.0×108 min−1, with the overall reaction order at nearly 2.5. The prediction curves, based on Friedman method and autocatalytic model, were in good agreement with the experimental data.